Association of dynamic changes in metabolic syndrome components with clinical outcomes in diffuse large B-cell lymphoma - Zhao, Dewan; Xu, He; Tang, Fengrao; Cui, Tongcheng; Sun, Xiuli; Song, Guirong (Frontiers in Oncology, 2025)
IntroductionDiffuse Large B-Cell Lymphoma (DLBCL) is the most common subtype of Non-Hodgkin Lymphoma (NHL), with 20-40% of patients experiencing poor outcomes despite advancements in treatment. While Metabolic Syndrome (MetS) has been linked to NHL prognosis, its impact on DLBCL outcomes remains unclear.MethodsThis study examined the effects of dynamic changes in MetS components on DLBCL treatment outcomes and prognosis. We retrospectively analyzed 125 newly diagnosed DLBCL patients treated with 6-8 cycles of CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) or CHOP-like regimens, with or without rituximab, from May 2010 to May 2022. Group-based trajectory models were used to identify MetS component trajectories. Multivariate logistic regression and Cox proportional hazards regression were employed to determine factors affecting complete remission (CR), progression-free survival (PFS), and overall survival (OS).ResultsThe 2-year PFS and OS rates were 70.0% and 82.0%, respectively. High baseline high-density lipoprotein cholesterol (HDL-C) was associated with reduced progression risk (HR = 0.27, 95% CI: 0.10-0.78), while high baseline low-density lipoprotein cholesterol (LDL-C) was linked to decreased CR rate (OR = 0.65, 95% CI: 0.44-0.97) and increased progression risk (HR = 1.78, 95% CI: 1.14-2.79). Additionally, high LDL-C trajectory was associated with reduced CR rates, whereas moderate BMI trajectory was associated with improved CR, PFS, and OS.DiscussionTherefore, controlling LDL-C levels and maintaining a moderate BMI are crucial for improving DLBCL clinical outcomes.